Peran Harun al-Rasyid terhadap Pendidikan Islam di Era Daulah Abbasiah - Fadhlurrahman Fadhlurrahman; Abd. Rachman Assega (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
This article will examine the thoughts of the caliph Harun al-Rasyid about the concept of Islamic education that he initiated. He succeeded in establishing the “Baitul Hikmah” library which became an icon in the golden age of Islam in the Abbasid Period. In fact, this library is a symbol of civilization and the center of Islamic world enlightenment for Western civilization. Interestingly, this library is also the center of translation and copying of ancient Greek, Persian and other intellectual legacies. This is evidence of the success of Harun al-Rasyid’s ideas in the world of Islamic education. This research uses descriptive analysis method to explain Harun al-Rasyid’s thoughts on Islamic education, then the content analysis method is used to find the basic ideas and concepts of development in the future. After conducting research, the authors conclude that the successful application of his thought to Islamic education cannot be separated from his great attention to science. Even with the advancement of science, the economy of the people at that time became advanced. This research is very important to be learned as through this research can discoverd a very brilliant thought of the great chaliph Harun al-Rasyid.